PMA522 : Postpress process / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
Binding and finishing is related to the finished work of any printing process. It also covers the early history of how people started to compile documents and also the technical of proper binding method. The teaching method is by having the materials and machines demonstrated, its functions and usage to the students as well as how, the raw materials reaches the end process which is the post press section. Assignments and practical-work shall be conducted from time to time in ensuring that the students understand well. Hands-on activities are important in helping the students to familiarize the process stages.